RELEVANCE OF PERSONALITY STYLES AND PERSONAL GOALS IN THE PREDICTION OF LIFE SATISFACTION - Díaz Morales, Juan Francisco; Sánchez-López, Mª Pilar (Anales de Psicología / Annals of Psychology, 2001)
In this article is examined the personality style and personal goal roles in the prediction of life satisfaction. At present, the personality is considered like a complex system which can be analysed from different levels and unities of analysis. The personality styles represent the most stable unities while the goals are considered like mediating process which represent the most dynamic part of the personality. Different authors see the relationship between these unities like an approach to the study of personality coherence. The study of variables related to well-being allows to analyse the relationship between different analysis unities (styles and goals), just as it’s showed in Little’s ecologicalsocial model (1999). Subjects are 120 argentine women. The instrument used are Millon’s Index of Personality Styles (MIPS) (Millon, 1994), the evaluation of different dimensions of personal goals, and the Satisfaction With the Life Scale (SWLS) (Diener, Emmons, Larsen y Griffin, 1985). The results indicate that the mediating process (personal goals) and dispositions (personality styles) allow to predict a high percentage of variance of satisfaction. The family support and the orientation of pleasure show a close relationship with life satisfaction.